Building Filipiniana indexes towards the development of a standard Filipiniana subject heading list - Vesagas, Terence John C. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
This research was conducted to explore the creation of Filipiniana indexes as part of an effort to push for the eventual creation of a standardized Filipiniana Subject Heading List. As there is no existing subject heading system or index based on the Filipiniana, this research aimed to push forward in the formation of a localized system by creating indexes for the Filipiniana collection. These indexes provides the first step towards subject analysis through the provision of key terms and contexts gained through the processing of the collection. With the growth of technology, methods such as automatic indexing have become a point of interest. This is because automatic indexing makes use of computational power to perform large-scale tasks with ease. Thus, big data analysis tools were used as the primary instrument to process the raw data and produce the final outputs. The UP Filipiniana collection was chosen for this research as it has the largest collection of Filipiniana materials in the country.